Arthritis patients’ experience and perception of therapeutic gloves - Nasir, S. H.; Troynikov, O.; Massy-Westropp, N. (Taylor and Francis, 2017)
Therapeutic gloves are widely used to manage arthritis patients’ hand symptoms and improve their hand function, but patients’ experience and perception towards the gloves are poorly understood. This research sought to gain insight into patients’ experience of wearing therapeutic gloves, their perceptions of the gloves and their preference in terms of glove design. Thirty arthritis patients who used therapeutic gloves as part of their rehabilitation treatment were surveyed. Adherence in wearing was good with 80% of the participants wore the gloves up to 8 hours a day. Most respondents found therapeutic gloves were soft to the skin and believed that they were effective. Problems identified included gloves leaving marks on the skin and itchy hands after gloves removal. The key characteristics identified by participants on gloves design will facilitate manufacturers and clinicians to improve the existing gloves in order to enhance its functions, comfort and users’ needs.